Efficient Light-Induced Phase Transitions in Halogen-Bonded Liquid Crystals - Fernandez-Palacio, Francisco (Chem Mater, 2016)
[Image: see text] Here, we present a new family of light-responsive, fluorinated supramolecular liquid crystals (LCs) showing efficient and reversible light-induced LC-to-isotropic phase transitions. Our materials design is based on fluorinated azobenzenes, where the fluorination serves to strengthen the noncovalent interaction with bond-accepting stilbazole molecules, and increase the lifetime of the cis-form of the azobenzene units. The halogen-bonded LCs were characterized by means of X-ray diffraction, hot-stage polarized optical microscopy, and differential scanning calorimetry. Simultaneous analysis of light-induced changes in birefringence, absorption, and optical scattering allowed us to estimate that <4% of the mesogenic units in the cis-form suffices to trigger the full LC-to-isotropic phase transition. We also report a light-induced and reversible crystal-to-isotropic phase transition, which has not been previously observed in supramolecular complexes. In addition to fundamental understanding of light-responsive supramolecular complexes, we foresee this study to be important in the development of bistable photonic devices and supramolecular actuators.